Faculty of Pharmacy, UiTM partners with Rhazes to enhances telepharmacy competency / Zakiah Mohd Noordin, Assoc. Prof. Dr. Mahmathi Karuppannan and Dr. Gurmeet Kaur Surindar Singh - Mohd Noordin, Zakiah; Karuppannan, Mahmathi; Surindar Singh, Gurmeet Kaur (Faculty of Pharmacy, 2023)
On May 29 and June 10, 2023, ten lecturers from the Department of Clinical Pharmacy, Faculty of Pharmacy, UiTM Puncak Alam took part in a telepharmacy virtual Objective Structured Clinical Examination (OSCE) session conducted as part of the Rhazes Telepharmacy International Virtual Internship programme. This innovative initiative provided a platform for lecturers to evaluate students'practical, professional, and communication competencies to provide pharmaceutical care via telepharmacy. The telepharmacy OSCE focuses on assessing their ability to provide patient counselling, medication reviews, and recommendations via telecommunication platforms. With the growing popularity of telehealth services, it is imperative for pharmacy graduates to possess the necessary skills to deliver pharmaceutical care remotely.